2013
DOI: 10.1002/iub.1171
|View full text |Cite
|
Sign up to set email alerts
|

Uridine adenosine tetraphosphate induces contraction of circular and longitudinal gastric smooth muscle by distinct signaling pathways

Abstract: Extracellular nucleotides uridine-5 0 -triphosphate (UTP) and adenosine-5 0 -triphosphate (ATP) induce contraction of gastric smooth muscle (SM). The dinucleotide uridine adenosine tetraphosphate (Up 4 A), an endothelium-derived contraction factor, induces vascular SM contraction. Its effect on gastric SM contractions, however, is unknown. We addressed the hypothesis that Up 4 A induces gastric SM contraction via a mechanism that may differ between circular and longitudinal muscle (CM and LM, respectively). CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Several subsequent studies have confirmed that Up 4 A produces vasoconstriction in rat renal artery (3), aorta (5), gastric smooth muscle (29) and pulmonary arteries (6). Furthermore, vasoconstriction was observed in mouse renal arterioles (7) and aorta (8).…”
Section: Discussionmentioning
confidence: 89%
“…Several subsequent studies have confirmed that Up 4 A produces vasoconstriction in rat renal artery (3), aorta (5), gastric smooth muscle (29) and pulmonary arteries (6). Furthermore, vasoconstriction was observed in mouse renal arterioles (7) and aorta (8).…”
Section: Discussionmentioning
confidence: 89%
“…Up4A is likely associated with blood pressure regulation, because its levels in plasma are elevated in hypertensive subjects (3) and it causes vasoconstriction in deoxycorticosterone acetate-salt hypertensive rats (4) and type 2 diabetic rats (5). Up4A also contracts rat and human airways (6) and rat gastric smooth muscles (7). Pharmacological studies suggest that Up4A causes vasoconstriction via activation of P2X1, P2Y2, and P2Y4 receptors (1) and endothelium-dependent vasodilatation via activation of P2Y1 and P2Y2 receptors (8).…”
mentioning
confidence: 99%
“…Cytidine-5′-diphosphocholine, an endogenous nucleotide, used for the treatment of neurodegenerative disorders, produced contractions of mouse gastric fundus through, at least in part, purinoceptors and Rho/Rho kinase signalling [303]. Uridine adenosine tetraphosphate produces contraction of gastric smooth muscle via P2Y receptors [744].…”
Section: Receptor Identificationmentioning
confidence: 99%